2021
DOI: 10.1089/aut.2020.0050
|View full text |Cite
|
Sign up to set email alerts
|

Coproduction with Autistic Adults: Reflections from the Authentistic Research Collective

Abstract: This article explores coproduction in relation to autistic people. We reflect on the coproduction process with autistic adults from the Authentistic Research Collective at University College London. We aimed to support the autistic population's mental health needs by coproducing a document on adapting psychological therapy, and by developing a set of reflective guidelines to guide and encourage future coproduction initiatives between autistic and nonautistic team members. We reflect upon six elements that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…This aspect of our findings is in line with findings of other critical autism studies that suggested that learning about one’s autism positively transforms concepts of self, such as realizing that autistic behaviors, which look abnormal, are normal behaviors of autistic people (Seers & Hogg, 2021; Tan, 2018), whose needs for their surroundings are different from those of the majority of society who generally does not have autistic characteristics, including sensory sensitivity and social communication difficulty. Our findings on IoS as an authentically autistic way of coping also tie well with the recently growing autism literature on authenticity, wherein authenticity is discussed as an important but overlooked element to consider regarding autistic adults (Bottema-Beutel et al, 2018; Stark et al, 2021). Future empirical research that asks autistic adults about the relationship between IoS and being authentically autistic would be welcome.…”
Section: Discussionsupporting
confidence: 85%
“…This aspect of our findings is in line with findings of other critical autism studies that suggested that learning about one’s autism positively transforms concepts of self, such as realizing that autistic behaviors, which look abnormal, are normal behaviors of autistic people (Seers & Hogg, 2021; Tan, 2018), whose needs for their surroundings are different from those of the majority of society who generally does not have autistic characteristics, including sensory sensitivity and social communication difficulty. Our findings on IoS as an authentically autistic way of coping also tie well with the recently growing autism literature on authenticity, wherein authenticity is discussed as an important but overlooked element to consider regarding autistic adults (Bottema-Beutel et al, 2018; Stark et al, 2021). Future empirical research that asks autistic adults about the relationship between IoS and being authentically autistic would be welcome.…”
Section: Discussionsupporting
confidence: 85%
“…Conceivably, in practice, this means some autistic individuals may not be offered EMDR even if this is potentially indicated as a treatment option. Clients should ideally have opportunities for informed discussions with therapists about which therapeutic approach may be a good fit for them ( Stark et al, 2020 ), why (e.g. based on presenting problems, goals for intervention, the evidence base) and how to evaluate if this is the case.…”
Section: Discussionmentioning
confidence: 99%
“…Training in co-production (a ‘co-production curriculum’) may support success [ 53 ]. However, co-production with autistic people also needs to consider their specific needs, including ways to support different communication preferences and consideration of necessary environmental adaptations [ 54 ].…”
Section: Discussionmentioning
confidence: 99%